Expansive Mappings and Their Applications in Modular Space - A. Azizi; R. Moradi; A. Razani (Abstract and Applied Analysis)
Some fixed point theorems for ρ-expansive mappings in modular spaces are presented. As an application, two nonlinear integral equations are considered and the existence of their solutions is proved.